2022
DOI: 10.3390/biom12060749
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 and Serotonin 5-HT1A Dimeric Receptor-Binding Monomeric Antibody scFv as a Potential Ligand for Carrying Drugs Targeting Selected Areas of the Brain

Abstract: Targeted therapy uses multiple ways of ensuring that the drug will be delivered to the desired site. One of these ways is an encapsulation of the drug and functionalization of the surface. Among the many molecules that can perform such a task, the present work focused on the antibodies of single-chain variable fragments (scFvs format). We studied scFv, which specifically recognizes the dopamine D2 and serotonin 5-HT1A receptor heteromers. The scFvD2–5-HT1A protein was analyzed biochemically and biologically, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 97 publications
(127 reference statements)
0
1
0
Order By: Relevance
“…The ideal biomaterials applied in repairing SCI should have good cytocompatibility. The PC-12 cell line was isolated from the rat adrenal pheochromocytoma and has an embryonic origin from the neural crest. , PC-12 cells were involved in many in vitro neurobiological studies because they retained the characteristics of dopaminergic neurons. , Gel and MH@BP Gel leaching solution-treated PC-12 cells had viabilities of 108.59% and 93.47%, respectively, while MH Gel leaching solution-treated cells had viability of only 7.62% (Figure G). Live/dead cell staining images demonstrated that there were almost no dead cells in the Gel group and MH@BP Gel group (Figure H).…”
mentioning
confidence: 99%
“…The ideal biomaterials applied in repairing SCI should have good cytocompatibility. The PC-12 cell line was isolated from the rat adrenal pheochromocytoma and has an embryonic origin from the neural crest. , PC-12 cells were involved in many in vitro neurobiological studies because they retained the characteristics of dopaminergic neurons. , Gel and MH@BP Gel leaching solution-treated PC-12 cells had viabilities of 108.59% and 93.47%, respectively, while MH Gel leaching solution-treated cells had viability of only 7.62% (Figure G). Live/dead cell staining images demonstrated that there were almost no dead cells in the Gel group and MH@BP Gel group (Figure H).…”
mentioning
confidence: 99%